Reisen zu den Quellen des Tigris ... Studien von Josef Wünsch in Mesopotamien (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Josef Wünsch (1842 - 1907) undertook a three-year research activity in the eastern provinces of the Ottoman Empire. In this volume his estate (cartographic and ethnographic works and collections) is brought together and evaluated from today's scientific point of view